Effectiveness of the misoprostol for the abortion in the first trimester of the pregnancy in adolescents. - Práxedes Rojas Quintana; Pedro Ayo Naranjo; Alberto Jorge Fernández; Israel Sotolongo Castro; Joan Hernández Cabrera; Annia Najarro (Medisur)
Background: Synthetic prostaglandin PGE1 known ad misoprostol is an analog of the E prostaglandin. In the gynecological field it is used for the cervix uterine maturation and in this way it provokes modifications which favor the fast expel of the product of conception in the first trimester of pregnancy. Objectives: to show the effectiveness of misoprostol for medicamentous abortion in the first trimester of adolescents´ pregnancy. Methods: a descriptive, series cases, prospective study which included 763 adolescents in Cienfuegos province from August 2005 to June 2007. Adolescents with their parents' consent asked the doctors for the interruption of their pregnancy status using misoprostol as medicamentous abortion. For the performance of this method, a methodological instrumentation guide created by the Public Health Minister for the usage of misoprostol in vaginal pathway for the abortion induction was used. Results: The expelling of the fetus was successful in 93, 4 % of the adolescents, 66% of them were in their 8 weeks of gestation, 89 % were nulliparae, and 2, 6 were multiparae. The most frequent symptoms produced for this method were bleeding (42%), and pain (38, 4%). Conclusions: the usage of misoprostol was effective for the interruption of pregnancy in the first trimester in adolescents.